Polyimide / polydimethylsiloxane super-hydrophobic composite coating and preparation method thereof

Through the preparation of polyimide/polydimethylsiloxane superhydrophobic composite coating, combined with modified GO and fluorinated SiO2, a multi-layer coating was constructed, which solved the problem of insufficient anti-corrosion performance of the existing coating and achieved the Efficient anti-corrosion and stain-proof and self-cleaning effect.

CN119307177AActive Publication Date: 2025-01-14SHAANXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202411674655.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-01-14
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The existing superhydrophobic composite coatings have long-term shortcomings in corrosion resistance, and do not have self-cleaning and anti-fouling properties, making it difficult to meet the anti-corrosion and anti-fouling requirements in complex environments.

Method used

The polyimide/polydimethylsiloxane superhydrophobic composite coating is prepared by solution condensation and polymerization is made into a polyimide/polydimethylsiloxane prepolymer, and modified GO is added thereto. A composite bottom layer is formed, and then a fluorinated modified SiO2 suspension is applied to the surface of the composite bottom layer, and a multi-layer superhydrophobic coating is constructed to enhance anti-corrosion and stain resistance.

Benefits of technology

It has achieved the improvement of long-term anti-corrosion performance, has self-cleaning and anti-fouling properties, enhances the mechanical properties and durability of the coating, effectively prevents the penetration of corrosive ions through the series barrier and maze effect, and reduces stain adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a polyimide / polydimethylsiloxane super-hydrophobic composite coating and a preparation method thereof.The preparation method comprises the steps that firstly, under nitrogen protection, diamine monomers and polydimethylsiloxane are dissolved in an organic solvent, then dianhydride monomers are added in batches, stirring reaction is conducted, and a polyimide / polydimethylsiloxane prepolymer is prepared; adding an organic dispersion liquid of modified GO into the polyimide / polydimethylsiloxane prepolymer to prepare composite bottom layer slurry, coating the surface of a base material with the composite bottom layer slurry, and performing programmed thermal imidization treatment to prepare a composite bottom layer; and coating the surface of the composite bottom layer with a suspension of an adhesive and fluorinated modified SiO2, and curing at room temperature to obtain the polyimide / polydimethylsiloxane super-hydrophobic composite coating. The composite coating has good long-acting corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of development of super-hydrophobic coatings and relates to a polyimide / polydimethylsiloxane super-hydrophobic composite coating and a preparation method thereof. Background Art

[0002] The superhydrophobic phenomenon in nature is ubiquitous, such as the self-cleaning effect of lotus leaves. Studies have found that the reason why lotus is superhydrophobic is that the surface of lotus leaves has a large number of micro-nanostructured "papillaries" and paraffin substances, which together constitute the superhydrophobic effect of lotus leaves. Inspired by the lotus leaf effect, many scientific researchers have prepared superhydrophobic anti-corrosion and antifouling coatings based on the characteristics of superhydrophobic surface construction. This coating has a significant repulsive effect on various liquids. By reducing the contact area, it can delay or prevent corrosive ions from passing through the coating to reach the surface of the substrate and cause electrochemical corrosion. In recent years, superhydrophobic coatings have important application prospects in the fields of self-cleaning, anti-icing, anti-corrosion, oil-water separation, and anti-bacterial adhesion. At present, there are two conditions for constructing superhydrophobic coatings: one is that the surface of the material has low surface energy substances, and the other is that the surface has a rough structure. For example, Liu et al. used a method combining etching process and high-temperature calcination to prepare a superhydrophobic surface on a copper sheet. They found that when the etching time was 20 hours and the calcination temperature was 340°C, the micro-nanostructure on the surface of the copper sheet was relatively rough. They then used stearic acid to hydrophobize it and finally obtained a superhydrophobic surface with a contact angle of 157.6°.

[0003] At present, traditional composite coatings rely on their excellent physical barrier effect to have anti-corrosion properties, but there is a common problem that the long-term anti-corrosion performance is seriously insufficient. Moreover, this type of coating itself does not have self-cleaning and anti-fouling properties, and it is difficult to meet the anti-corrosion and anti-fouling requirements in complex environments. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a polyimide / polydimethylsiloxane super-hydrophobic composite coating and a preparation method thereof, thereby solving the technical problem of insufficient long-term anti-corrosion performance of the composite coating in the prior art.

[0005] The present invention is achieved through the following technical solutions: A method for preparing a polyimide / polydimethylsiloxane super-hydrophobic composite coating comprises the following steps: S1: Under nitrogen protection, dissolving diamine monomer and polydimethylsiloxane in an organic solvent, then adding dianhydride monomer in batches, stirring and reacting, to obtain a polyimide / polydimethylsiloxane prepolymer; S2: adding the organic dispersion of modified GO to the polyimide / polydimethylsiloxane prepolymer to obtain a composite bottom layer slurry, coating the composite bottom layer slurry on the surface of the substrate, and obtaining a composite bottom layer after a program thermal imidization treatment; the modification reagent of the modified GO includes at least one of POSS, a silane coupling agent, a chain alkyl amine and a chain alkyl isocyanate, and the number of carbon atoms on the chain alkyl in the chain alkyl amine and the chain alkyl isocyanate is 7 to 18; S3: coating the adhesive and the suspension of fluorinated modified SiO2 on the surface of the composite bottom layer, and curing at room temperature to obtain the polyimide / polydimethylsiloxane super-hydrophobic composite coating.

[0006] Preferably, the polydimethylsiloxane accounts for 10% to 30% of the total mass of the diamine monomer and the dianhydride monomer.

[0007] Preferably, the diamine monomer is a fluorine-containing diamine monomer and / or the dianhydride monomer is a fluorine-containing dianhydride monomer.

[0008] Preferably, in the modified GO, the mass ratio of the modifying agent to GO is 1wt%~6.5wt%.

[0009] Preferably, in step S2, the mass fraction of the modified GO in the polyimide / polydimethylsiloxane prepolymer is 0.01wt%~1.50wt%.

[0010] Preferably, the thickness of the composite bottom layer is 40-50 μm.

[0011] Preferably, the preparation process of the fluorinated modified SiO2 is: adding sodium methylsiliconate to a dispersion of SiO2 particles, stirring evenly, adding 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane and tetraethoxysilane, stirring and reacting at room temperature to obtain the fluorinated modified SiO2; the SiO2 particles include at least one of a particle size of 7~500nm and 2~20μm; when the SiO2 particles have a particle size of 7~500nm and 2~20μm, the mass percentage of SiO2 particles with a particle size of 7~500nm is 70%~85%, and the mass percentage of SiO2 particles with a particle size of 2~20μm is 15%~30%.

[0012] Preferably, in the suspension of the adhesive and fluorinated modified SiO2, the fluorinated modified SiO2 accounts for 0.01wt%~1.50wt% of the mass of the adhesive.

[0013] Preferably, in step S3, before coating the adhesive and the suspension of fluorinated modified SiO2 on the surface of the composite substrate, a PU intermediate layer is coated on the surface of the composite substrate, and then the adhesive and the suspension of fluorinated modified SiO2 are coated.

[0014] A polyimide / polydimethylsiloxane super-hydrophobic composite coating is prepared by the above method; the contact angle of the composite coating is 153-162°, and after a 90-day neutral salt spray test, the low-frequency impedance value of the composite coating is 9.81× 10 9 Ω⋅cm 2。

[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a preparation method of a polyimide / polydimethylsiloxane super-hydrophobic composite coating. The method comprises the following steps: firstly synthesizing a polyimide / polydimethylsiloxane prepolymer by solution polycondensation, then adding modified GO to the prepolymer to obtain a composite bottom layer slurry, wherein the modifying agent of the modified GO comprises at least one of POSS, a silane coupling agent, a chain alkylamine and a chain alkyl isocyanate, wherein the number of carbon atoms on the chain alkyl in the chain alkylamine and the chain alkyl isocyanate is 7 to 18; in the bottom layer solution, the polyimide has good hydrophobicity and good moldability, while the polydimethylsiloxane has strong adhesion to a metal substrate. The invention discloses a method for preparing a polyimide / polydimethylsiloxane super-hydrophobic composite coating. The method comprises the steps of: applying a suspension of adhesive and fluorinated modified SiO2 on the surface of the composite bottom layer, and curing the suspension at room temperature to obtain the polyimide / polydimethylsiloxane super-hydrophobic composite coating. The suspension of adhesive and fluorinated modified SiO2 is used as the top coating. The fluorinated modified SiO2 has good super-hydrophobicity, which can effectively reduce the contact area between the coating and the aqueous solution and enhance the blocking effect on corrosive ions. At the same time, the super-hydrophobic layer of the top layer has quasi-isotropic characteristics and excellent mechanical properties, which makes the coating more durable. A multilayer superhydrophobic coating was successfully constructed by constructing a modified GO / polyimide / polydimethylsiloxane composite bottom layer and a fluorinated modified SiO2 surface layer. The anti-corrosion and anti-fouling mechanism of the multilayer superhydrophobic coating is as follows: first, "series" layer-by-layer barrier barriers. The bottom composite coating and the surface superhydrophobic coating constitute a series barrier barrier, which increases the penetration path of corrosive ions and forms a "maze effect" to effectively enhance the corrosion resistance; secondly, the superhydrophobic surface is anti-corrosive and anti-fouling. The micro / nanostructure of the superhydrophobic surface reduces the contact area with the corrosive medium by forming an "air cushion effect" on its surface, greatly enhancing the anti-corrosion performance, while the low surface energy characteristics of the top superhydrophobic coating reduce the adhesion of stains, playing an anti-fouling and self-cleaning role; finally, through the effective combination of surface interface technology and bionic strategies, a multilayer composite superhydrophobic coating is constructed to obtain a superhydrophobic coating with excellent mechanical properties.

[0016] Furthermore, the diamine monomer is a fluorine-containing diamine monomer and / or the dianhydride monomer is a fluorine-containing dianhydride monomer, which can effectively improve the hydrophobicity of the composite coating and enhance its long-term corrosion resistance.

[0017] Furthermore, in step S3, before coating the adhesive and the suspension of fluorinated modified SiO2 on the surface of the composite bottom layer, a PU intermediate layer is coated on the surface of the composite bottom layer, and then the adhesive and the suspension of fluorinated modified SiO2 are coated. Here, the PU intermediate layer serves as an intermediate transition bonding layer, which allows the super-hydrophobic layer of the top layer to be embedded in the intermediate layer, effectively improving the adhesion between the bottom layer and the top layer, and effectively improving the long-term anti-corrosion performance of the composite coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0019] Figure 1 is an infrared spectrum of the fluorinated polyimide / polydimethylsiloxane composite coating prepared in Example 1 of the present invention; Figure 2 The corrosion performance of the fluorinated polyimide / polydimethylsiloxane composite coating prepared in Example 1 of the present invention, wherein the left figure is a Nyquist diagram and the right figure is a Bode diagram; Figure 3 The corrosion performance of the polyimide (non-fluorine-containing) / polydimethylsiloxane composite coating prepared in Example 3 of the present invention, wherein the left figure is a Nyquist diagram and the right figure is a Bode diagram; Figure 4 The corrosion performance of the polyimide (non-fluorine-containing) / polydimethylsiloxane composite coating prepared in Example 5 of the present invention, wherein the left figure is a Nyquist diagram and the right figure is a Bode diagram; Figure 5 The corrosion resistance of the double-layer super-hydrophobic coating prepared in Example 1 of the present invention is shown in the figure on the left, wherein the Nyquist diagram is shown and the Bode diagram is shown on the right; Figure 6 The microscopic morphologies (a-c) and contact angles (d) of the double-layer super-hydrophobic coating prepared in Example 1 of the present invention at different magnification ratios, wherein in Figure (d), CA on the right is the static contact angle, and SA is the rolling contact angle. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0021] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0022] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible sub-ranges and individual values ​​within the range (including integers and fractions).

[0023] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0024] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0025] The present invention provides a method for preparing a polyimide / polydimethylsiloxane super-hydrophobic composite coating, comprising the following steps: S1: Under nitrogen protection, diamine monomer and polydimethylsiloxane are dissolved in an organic solvent, and then dianhydride monomer is added in batches, stirred for reaction, and polycondensation of a polyimide / polydimethylsiloxane prepolymer with a solid content of 10% to 50% is prepared; The polydimethylsiloxane accounts for 10% to 30% of the total mass of the diamine monomer and the dianhydride monomer.

[0026] The diamine monomers are 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 4,4'-(1,4-phenylenedioxy)dianiline, 4,4'-diaminodiphenylmethane, 1,4-phenylenediamine, N-phenyl-1,4-phenylenediamine, 2,2'-bis[4-(4-aminophenoxyphenyl)]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis[4-(2-trifluoromethyl-4-aminophenoxy)phenyl]propane, 2,2-[4-(2- 4,4'-bis(2-trifluoromethyl-4-aminophenoxy)benzophenone, 4,4'-bis(2-trifluoromethyl-4-aminophenoxy)diphenyl sulfone, 4,4'-bis(2-trifluoromethyl-4-aminophenoxy)diphenyl sulfide, 4,4'-bis(2-trifluoromethyl-4-aminophenoxy)biphenyl, 1,3-bis(2-trifluoromethyl-4-aminophenoxy)benzene, 1,4-bis(2-trifluoromethyl-4-aminophenoxy)benzene, 1,3-bis[3'-trifluoromethyl-4'(4''-aminophenoxy)phenyl]benzene, 1,3-bis(4-amino-2-trifluoromethylphenoxy)benzene, 4,4''-bis(aminophenoxy)-3,3'-trifluoromethylterphenyl, 4 , one or more of 4-bis[3'-trifluoromethyl-4'(4''-aminophenoxy)phenyl]biphenyl.

[0027] The dianhydride monomers are 4,4'-oxydiphthalic anhydride, 4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride), pyromellitic anhydride, biphenyltetracarboxylic anhydride, triphenyl ether carboxylic anhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]hexafluoropropane dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)phthalic anhydride, 1,3- One or more of bis(3,4-dicarboxyphenoxy)phthalic anhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenyl sulfone dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)benzophenone dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride, and 4,4'-bis(3,4-dicarboxyphenoxy)diphenyl ether dianhydride.

[0028] The diamine monomer is preferably a fluorine-containing diamine monomer and / or the dianhydride monomer is a fluorine-containing dianhydride monomer.

[0029] The organic solvent is a high boiling point organic solvent, which may be at least one of N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO) and diacetone alcohol.

[0030] S2: 0.1-10 mg of modified GO is added to 1.0 mL of an organic solvent, wherein the organic solvent is at least one of N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO) and diacetone alcohol, and then ultrasonically dispersed for 10-60 min to obtain an organic dispersion of modified GO, i.e., a functional filler pre-dispersion liquid. The organic dispersion of modified GO is then added to the polyimide / polydimethylsiloxane prepolymer, and ultrasonically dispersed for 15-60 min to obtain a composite bottom layer slurry with a solid content of 8%-20%, i.e., a polyimide / polydimethylsiloxane prepolymer composite slurry containing modified GO. The composite bottom layer slurry is coated on the surface of the substrate. At room temperature, the sprayed sample is placed for 1-2 hours to achieve surface drying. After a program thermal imidization treatment, a thickness of 1-150 μm, preferably 10-100 μm, is obtained. μm, preferably 40-50 μm thick, more preferably 38-42 μm thick composite bottom layer, i.e. polyimide / polydimethylsiloxane composite coating. The thermal imidization process includes volatilizing a large amount of solvent at 80°C-135°C, preferably curing at 135°C for 3 h, then completing imidization at 200-300°C, performing preliminary imidization at 200°C (2 h), and completing more thorough imidization at 240-300°C due to different imide systems, and curing for about 1 h.

[0031] The modification agent for modifying GO includes at least one of POSS, a silane coupling agent, a chain alkylamine and a chain alkyl isocyanate, wherein the number of carbon atoms on the chain alkyl in the chain alkylamine and the chain alkyl isocyanate is 7 to 18; The POSS is an oligomeric silsesquioxane, which may include any one of monoamino oligomeric silsesquioxane, diamino oligomeric silsesquioxane and octaamino oligomeric silsesquioxane; The silane coupling agent includes 1h,1h,2h,2h-perfluorodecyltriethoxysilane, 1h,1h,2h,2h-perfluorodecyltrimethoxysilane, 3-aminopropylmethyltrimethoxysilane, 3-aminopropylmethyltriethoxysilane, N-2-aminoethyl-3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-aminoethyl-3-aminopropyltriethoxysilane, dodecyltrimethoxysilane and hexadecyltrimethoxysilane; The chain alkane includes an alkylamine having 7 to 18 carbon atoms, preferably, dodecylamine or hexadecylamine.

[0032] In the modified GO, the modifier is chemically grafted to the GO surface by covalent bonding; In the modified GO, the mass ratio of the modifying agent to GO is 1 wt% to 6.5 wt%, and preferably, the mass ratio of the modifying agent to GO is 2.5 wt% to 3.0 wt%.

[0033] The mass fraction of the modified GO in the polyimide / polydimethylsiloxane prepolymer is 0.01wt%~1.50wt%, preferably 0.20wt%~0.80wt%, and more preferably 0.25wt%~0.60wt%.

[0034] The coating process here can be spraying or brushing. During the spraying process, after the composite bottom layer slurry is ultrasonically dispersed, it is sprayed on the metal substrate or the surface of the part under 0.2Mpa oil-free compressed air or compressed nitrogen, and the number of spraying times is 10 to 30 times, preferably 15 to 20 times. The caliber of the spraying equipment can be 0.5 mm; the substrate can be a metal substrate, and the metal substrate is an electrogalvanized steel plate, a 304 stainless steel plate, a cold-rolled plate, a galvanized steel plate, an aluminum alloy plate, an aluminum-magnesium alloy plate or a metal part of any shape.

[0035] In addition, when the composite base layer is coated on the surface of the substrate, the substrate is first pretreated, and the pretreatment includes degreasing, rust removal and ultrasonic cleaning.

[0036] The coating thickness was measured using a MINITEST 1100 coating thickness gauge.

[0037] Taking hexadecylamine as an example, in the modification process of GO, the process of chain alkylamine modification of GO can be as follows: 1.2 g of graphene oxide powder is uniformly dispersed in 2.4 L of deionized water, ultrasonically treated for 4 h (power 250 W), and then 6 mmol of hexadecylamine (HDA) and 360 mL of anhydrous ethanol are ultrasonicated in a conical flask for 30 min, slowly added to the graphene oxide suspension, and refluxed and stirred for 24 h. Centrifugation and washing with excess ethanol and distilled water are performed three times in sequence, and then freeze-dried and dried in a vacuum oven at 40°C overnight to evaporate the residual solvent to obtain the chain alkylamine modified GO.

[0038] S3: Coating a suspension of adhesive and fluorinated modified SiO2 on the surface of the composite base layer, and curing at room temperature for 24 hours to obtain the polyimide / polydimethylsiloxane super-hydrophobic composite coating. In this step, the curing temperature and time depend on the properties of the adhesive.

[0039] The super-hydrophobic SiO2 powder, i.e., fluorinated SiO2, is prepared by hydrolysis condensation. The specific preparation process is as follows: sodium methylsiliconate is added to the dispersion of SiO2 particles, and after stirring evenly, 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane and tetraethoxysilane are added, and the reaction is stirred at room temperature to obtain the fluorinated SiO2; the SiO2 particles include at least one of a particle size of 7 to 500nm and 2 to 20μm; when the SiO2 particles have a particle size of 7 to 500nm and 2 to 20μm, the mass percentage of SiO2 particles with a particle size of 7 to 500nm is 70% to 85%, and the mass percentage of SiO2 particles with a particle size of 2 to 20μm is 15% to 30%. The particles of 7 to 500nm here can also be mixed particles of multiple particle sizes.

[0040] The fluorinated modified SiO2 accounts for 0.01wt% to 1.50wt% of the mass of the adhesive, more preferably 0.30wt% to 1.50wt%, and more preferably 0.45wt% to 1.20wt%.

[0041] The preparation process of the adhesive and the suspension of fluorinated modified SiO2 is as follows: The adhesive is dissolved in a low boiling point solvent, and a semi-solid modified SiO2 containing anhydrous ethanol is added under continuous magnetic stirring, and stirring is continued to obtain a suspension of the adhesive and the fluorinated modified SiO2, that is, a uniform superhydrophobic suspension; Here, the low boiling point solvent is at least one of butyl acetate, ethyl acetate, acetone, furan, anhydrous ethanol, anhydrous methanol and the like.

[0042] The adhesive here is at least one of polyolefins, epoxies and acrylates.

[0043] In the step S3, before coating the adhesive and the suspension of fluorinated modified SiO2 on the surface of the composite substrate, a PU intermediate layer is coated on the surface of the composite substrate, and then the adhesive and the suspension of fluorinated modified SiO2 are coated.

[0044] A polyimide / polydimethylsiloxane super-hydrophobic composite coating is prepared by the above method; the contact angle of the composite coating is 153°~162°, and it still has good anti-corrosion performance after 90 days of neutral salt spray test, and its low-frequency impedance value is as high as 9.81 × 10 9 Ω⋅cm 2 , the composite coating still has superhydrophobic properties after more than 100 sandpaper abrasions and more than 80 tape glass mechanical tests.

[0045] The synthesized polyimide / polydimethylsiloxane super-hydrophobic composite coating has the intrinsic hydrophobicity of polyimide, because polydimethylsiloxane has hydrophobicity and strong corrosion resistance, polyimide can be non-fluorine-containing / fluorine-containing, and fluorine-containing polyimide and polydimethylsiloxane are low surface energy materials, the prepolymer has good interfacial compatibility and strong bonding force with components such as fillers and adhesives; polydimethylsiloxane has excellent bonding strength with metal substrates and low water absorption, and the polymer coating has excellent and lasting anti-corrosion and anti-fouling properties.

[0046] In addition, the polyimide / polydimethylsiloxane of the present invention combines a molecular structure of a polyimide hard segment and a polydimethylsiloxane soft segment, and has excellent mechanical properties, which are key factors determining the service life and performance of the anticorrosion and antifouling coating.

[0047] At the same time, the polyimide / polydimethylsiloxane prepared by the present invention has the anti-corrosion and anti-fouling properties of polyimide / polydimethylsiloxane, the barrier effect of modified GO and the shielding effect of polymer resin synergistically enhance the anti-corrosion performance of the coating, and the suspension prepared by spraying a commercial adhesive and super-hydrophobic modified SiO2 (F-SiO2) on the surface of the composite coating to construct a super-hydrophobic coating can give the coating an anti-fouling and self-cleaning effect. The process of this method is simple and easy to achieve large-scale production.

[0048] The invention discloses a preparation method and application of a polyimide / polydimethylsiloxane super-hydrophobic composite coating, belonging to the technical field of organic coatings. The preparation method comprises: synthesizing a polyimide / polydimethylsiloxane prepolymer; modifying a graphene oxide (GO) functional filler, wherein the modifying agent comprises: oligomeric silsesquioxane (POSS), a silane coupling agent, a long-chain alkane, etc.; according to the mass content of the functional filler and the polyimide / polydimethylsiloxane, a certain amount of the functional filler is pre-dispersed for 10 to 30 minutes and then mixed into the polyimide / polydimethylsiloxane prepolymer slurry and continued ultrasonic dispersion for 10 to 50 minutes to obtain a composite solution; the obtained functionalized graphene oxide polyimide / polydimethylsiloxane prepolymer mixed solution is sprayed on a metal substrate or a part surface by a spraying process, and then the composite coating is prepared by pre-curing at room temperature and temperature control at high temperature. A super-hydrophobic layer is further constructed on the surface of the obtained composite coating to obtain a double-layer or "sandwich" structured super-hydrophobic composite coating. That is, fluorinated siloxane or long-chain alkane siloxane is used to perform super-hydrophobic modification on micro-nano SiO2 of one particle size or different particle sizes to obtain super-hydrophobic nano SiO2 powder; secondly, an olefin adhesive of a preset mass ratio is dissolved in a low-boiling ester-based solvent, and the modified SiO2 semi-solid containing anhydrous ethanol is added to the adhesive-containing solution and stirred to obtain a super-hydrophobic suspension, and the super-hydrophobic SiO2 suspension is further sprayed on the surface of the composite coating using the same spraying process to prepare a super-hydrophobic composite coating, and after curing, a hydrophobic coating with a double-layer or "sandwich" structure of polyimide / polydimethylsiloxane composite layer as the base layer is obtained.

[0049] The present invention uses polyimide / polydimethylsiloxane composite coating as the bottom layer to prepare a double-layer or "sandwich" structure super-hydrophobic composite coating, and the prepared bottom composite layer has strong adhesion to the substrate, the top super-hydrophobic layer and the composite layer, or introduces a "sandwich" structure super-hydrophobic coating prepared by an intermediate transition layer, and each layer is firmly bonded. The design strategy of this super-hydrophobic coating has the advantages of being easy to prepare over a large area and having practical engineering application prospects, the preparation process is not limited by the metal substrate and the shape of the parts, the operability is strong, the components of the coating are simple, and it is easy to construct and apply and promote.

[0050] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0051] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0052] Example 1 (1) Preparation of GO Pre-oxidation of graphite powder: Add 30 ml of concentrated sulfuric acid to a 250 ml three-necked flask equipped with mechanical stirring under 25 °C water bath conditions, and add 5 g of natural flake graphene, 3 g of potassium persulfate, and 8 g of phosphorus pentoxide while stirring. Slowly increase the temperature to 60 °C for oxidation for 3 h, then cool to 25 °C and continue oxidation for 5 h. At the end of the experiment, filter and wash until the filtrate is neutral, and dry the product in a vacuum dryer at 50 °C for later use.

[0053] Under 25 ℃ water bath conditions, add 360 ml of concentrated sulfuric acid and 40 ml of phosphoric acid to a 500 ml three-necked flask equipped with mechanical stirring, add 3 g of pre-oxidized graphene under rapid stirring, mix well, and add 18 g of potassium permanganate powder within 2 hours. After the temperature of the reaction system is constant, heat it to 50 ℃ and maintain this temperature for 1 2 hours, then cool it to 25 ℃, then pour the reaction liquid into 400 ml of ice water under stirring, add 30% hydrogen peroxide solution to make the system bright yellow and no bubbles are generated, add an equal volume of 10% dilute hydrochloric acid solution, put it into a dialysis bag for dialysis, and dialyze until the dialysate is free of SO4 2- The ions are dialyzed and then concentrated by centrifugation, and the concentrate is freeze-dried to obtain GO.

[0054] (2) Preparation of single NH2-POSS modified graphene oxide (POSS-GO): 350 mg of graphene oxide, 5.0 g of NH2-POSS, 100 mg of dicyclohexylcarbodiimide and 50 mL of tetrahydrofuran were accurately weighed and dissolved in a 250 mL single-necked flask and ultrasonicated for 30 min. The above dispersion solution was then refluxed for 48 h, followed by rotary evaporation to remove the solvent and heat-treated at 120 °C for 12 h to obtain the product, which was labeled as POSS-GO. The above product was dissolved in 50 mL of tetrahydrofuran and precipitated in 500 mL of methanol. The experiment was repeated three times to remove the unreacted NH2-POSS, and then the final product was filtered using a 0.22 μm organic filter membrane, dried in a vacuum at 80 °C, and stored for later use.

[0055] (3) Synthesis of fluorinated polyimide / polydimethylsiloxane prepolymer: Under mechanical stirring and nitrogen protection, 3.885 g of 2,2-bis(4-aminophenyl)hexafluoropropane and 2.5 g of low molecular weight polydimethylsiloxane were dissolved in 55 g of DMAc, and 5.18 g of 4, 4'-(hexafluoroisopropylidene)diphthalic anhydride was added in batches at a constant temperature of 40 °C. After stirring for 6 h, the temperature was raised to 80 °C and the reaction was terminated for 2 h to obtain a fluorinated polyimide / polydimethylsiloxane prepolymer (solid content of 20 wt%).

[0056] (4) Preparation of fluorinated polyimide / polydimethylsiloxane composite coating: 4.0 mg of POSS-GO functional filler was added to 4 mL of DMAc and ultrasonically dispersed for 10 min, then added to 10 g of fluorinated polyimide / polydimethylsiloxane prepolymer and further dispersed for 30 min to obtain a composite mixed solution. The composite solution was sprayed on the surface of the substrate and subjected to thermal imidization at 135 (3 h), 200 (1 h), 280 ℃ (1 h) and 300 ℃ (1 h) to obtain a composite coating with a thickness of about 45 ± 5 μm.

[0057] (5) Preparation of double-layer super-hydrophobic coating: A double-layer super-hydrophobic coating was prepared on the surface of the composite coating in step (4), specifically, 1.2 g of POA adhesive and 1.0 g of F-SiO2 were dispersed in a mixed solution of butyl acetate and anhydrous ethanol, ultrasonically dispersed for 15 min and magnetically stirred for 30 min, and then sprayed on the surface of the composite coating to prepare a double-layer super-hydrophobic coating. The thickness of the super-hydrophobic layer was about 55 μm. Finally, the final super-hydrophobic coating was obtained after curing at room temperature for 24 h.

[0058] Among them, the preparation process of F-SiO2 is as follows: at room temperature, weigh 4 g of SiO2 nanoparticles of different particle sizes (including 2.4 g 15 nm SiO2, 0.8 g 30 nm, 0.8 g 5 μm SiO2, with mass contents of 60%, 20%, 20% respectively), 100 mL of anhydrous ethanol, and 20 mL of deionized water, stir at 500 r / min for 10 minutes, further ultrasonicate for 10 minutes, then add 3.0 g of sodium methylsiliconate and continue stirring for 10 min, finally add 750 μL 1H, 1H, 2H, 2H-perfluorodecyl triethoxysilane and 180 μL tetraethoxysilane to the above mixed solution, keep the reaction at room temperature for 4 h to ensure that the hydrolysis condensation reaction is complete. After the reaction, the product is centrifuged at a centrifugal speed of 10000 rpm for 10 min, washed with anhydrous ethanol and centrifuged three times. Then the obtained product is placed in a vacuum environment at 60 ° C for 12 h. Finally, fluorinated SiO2 nanoparticles were obtained, denoted by F-SiO2.

[0059] Example 2 (1) Preparation of GO Pre-oxidation of graphite powder: Add 30 ml of concentrated sulfuric acid to a 250 ml three-necked flask equipped with mechanical stirring under 25 °C water bath conditions, and add 5 g of natural flake graphene, 3 g of potassium persulfate, and 8 g of phosphorus pentoxide while stirring. Slowly increase the temperature to 60 °C for oxidation for 3 h, then cool to 25 °C and continue oxidation for 5 h. At the end of the experiment, filter and wash until the filtrate is neutral, and dry the product in a vacuum dryer at 50 °C for later use.

[0060] Under 25 ℃ water bath conditions, add 360 ml of concentrated sulfuric acid and 40 ml of phosphoric acid to a 500 ml three-necked flask equipped with mechanical stirring, add 3 g of pre-oxidized graphene under rapid stirring, mix well, and add 18 g of potassium permanganate powder within 2 hours. After the temperature of the reaction system is constant, heat it to 50 ℃ and maintain this temperature for 1 2 hours, then cool it to 25 ℃, then pour the reaction liquid into 400 ml of ice water under stirring, add 30% hydrogen peroxide solution to make the system bright yellow and no bubbles are generated, add an equal volume of 10% dilute hydrochloric acid solution, put it into a dialysis bag for dialysis, and dialyze until the dialysate is free of SO4 2- The ions are dialyzed and then concentrated by centrifugation, and the concentrate is freeze-dried to obtain GO.

[0061] (2) γ-Methacryloxypropyltrimethoxysilane (KH570) modified graphene oxide: 500 mg GO and 50 g anhydrous ethanol were added to a 250 mL single-necked flask and ultrasonicated for 30 min to obtain a dispersion. Subsequently, 3 g KH570 was added to the above dispersion and refluxed for 24 h to end the experiment. The product was washed alternately with deionized water and anhydrous ethanol three times and dried at 80 °C for 24 h to obtain KH570-modified graphene oxide, which was labeled as KH570-GO.

[0062] (3) Synthesis of polyimide (non-fluorinated) / polydimethylsiloxane prepolymer: Under mechanical stirring and nitrogen protection, 1.64 g of 4,4'-diaminodiphenyl ether and 1.8 g of low molecular weight polydimethylsiloxane were dissolved in 50 g of DMAc, and 5.32 g of 4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride) was added in batches at a constant temperature of 40°C. After stirring for 5 h, the temperature was raised to 70°C and the reaction was continued for 2 h to terminate the experiment. Polyimide / polydimethylsiloxane prepolymer (solid content of 20 wt.%) was obtained. Prepolymers with different contents of polydimethylsiloxane were prepared by the same method.

[0063] (4) Preparation of polyimide (non-fluorinated) / polydimethylsiloxane composite coating: 4.0 mg of KH570-GO functional filler was added to 4 mL of DMAc and ultrasonically dispersed for 10 min, then added to 10 g of polyimide / polydimethylsiloxane prepolymer and further dispersed for 30 min to obtain a composite mixed solution. The composite solution was sprayed on the surface of the substrate and subjected to thermal imidization at 135 (3 h), 200 (1 h), 280 ℃ (1 h) and 300 ℃ (1 h) to obtain a composite coating with a thickness of about 45 ± 5 μm.

[0064] (5) Preparation of double-layer super-hydrophobic coating: A double-layer super-hydrophobic coating was prepared on the surface of the composite coating prepared in step (4). Specifically, 1.2 g of POA adhesive and 1.0 g of F-SiO2 were dispersed in a mixed solution of butyl acetate and anhydrous ethanol, and then ultrasonically dispersed for 15 min and magnetically stirred for 30 min, and then sprayed on the surface of the composite coating to prepare a double-layer super-hydrophobic coating. The thickness of the super-hydrophobic layer was about 55 μm. Finally, the final super-hydrophobic coating was obtained after curing at room temperature for 24 h.

[0065] Among them, the preparation process of F-SiO2 refers to Example 1.

[0066] Example 3 The difference from Example 1 is that PU is sprayed on the surface of the composite coating prepared in step (4) as an intermediate transition layer, and then a mixed suspension of POA adhesive and F-SiO2 is sprayed on the surface of the intermediate transition layer, and cured at room temperature for 24 hours to obtain a "sandwich" structure super-hydrophobic coating. The thickness of the prepared intermediate transition layer is 10±5 μm, and the thickness of the super-hydrophobic layer (i.e., the mixed layer of POA adhesive and F-SiO2) is 40±5 μm.

[0067] Example 4 The difference from Example 2 is that PU is sprayed on the surface of the composite coating prepared in step (4) as an intermediate transition layer, and then a mixed suspension of POA adhesive and F-SiO2 is sprayed on the surface of the intermediate transition layer, and cured at room temperature for 24 hours to obtain a "sandwich" structure super-hydrophobic coating. The thickness of the prepared intermediate transition layer is 10±5 μm, and the thickness of the super-hydrophobic layer (i.e., the mixed layer of POA adhesive and F-SiO2) is 40±5 μm.

[0068] Example 5 Preparation of fluorinated polyimide / polydimethylsiloxane composite coating: 4.0 mg KH570-GO functional filler was added to 4 mL DMAc and ultrasonically dispersed for 10 min, then added to 10 g fluorinated polyimide / polydimethylsiloxane prepolymer and further dispersed for 30 min to obtain a composite mixed solution. The composite solution was sprayed on the surface of the substrate and subjected to thermal imidization at 135 (3 h), 200 (1 h), 280 ℃ (1 h) and 300 ℃ (1 h) to obtain a composite coating with a thickness of about 45±5μm.

[0069] In order to explore the performance of the composite coating prepared by the present invention, the following characterization tests were performed: According to GB / T6458.86 standard, the anti-corrosion, anti-fouling and self-cleaning performance of the composite coating prepared by the present invention is tested and analyzed, specifically: at 5.0 wt The neutral salt spray test was carried out in % NaCl solution, and the anti-corrosion performance of the coating was tested by electrochemical impedance spectroscopy at different intervals. The test frequency range was 10 -2 ~10 5 Hz, a sinusoidal disturbance with an amplitude of 10 mV. The equivalent circuit was fitted and analyzed using Z / Simp-Win software; Antifouling performance test of the coating: different stains were applied to the surface of the coating, and then the coating was slightly tilted at a certain angle and washed with water droplets. The test results are as follows: in, Figure 1 This is the infrared spectrum of the fluorinated polyimide / polydimethylsiloxane composite coating prepared in Example 1 of the present invention. As can be seen from the figure, the infrared spectrum at 2965 cm -1 The absorption peak at 1250 cm-1 is attributed to the asymmetric stretching vibration of -CH3. -1 、795 cm -1 The peaks at 1000 cm-1 are attributed to the bending vibration and stretching vibration of Si-CH3. -1 Up to 1100 cm -1 The strong peak at 1778 cm -1 The absorption peaks at 1720 cm-1 belong to the characteristic peaks of asymmetric and symmetric carbonyl stretching vibrations in the imine ring. FT-IR results show that the FPI-PDMS / POSS-GO composite coating was successfully prepared.

[0070] Figure 2 is the corrosion performance of the fluorinated polyimide / polydimethylsiloxane composite coating prepared in Example 1 of the present invention. As can be seen from the figure, the |Z| of the fluorinated polyimide / polydimethylsiloxane composite coating before the salt spray corrosion test is conducted. 0.01 HZ The value is 1.21 × 10 11 Ω∙cm 2.

[0071] Figure 3 is the corrosion performance of the polyimide (non-fluorine-containing) / polydimethylsiloxane composite coating prepared in Example 2 of the present invention. As can be seen from the figure, the |Z| of the polyimide (non-fluorine-containing) / polydimethylsiloxane composite coating before the salt spray corrosion test 0.01 HZ The value is 1.18 × 10 11 Ω∙cm 2 .

[0072] Figure 4 is the corrosion performance of the fluorinated polyimide / polydimethylsiloxane composite coating prepared in Example 5 of the present invention. As can be seen from the figure, the |Z| of the fluorinated polyimide / polydimethylsiloxane composite coating before the salt spray corrosion test is conducted. 0.01 HZ The value is 1.27 × 10 11 Ω∙cm 2 . Figure 5 The corrosion resistance of the double-layer super-hydrophobic coating prepared in Example 1 of the present invention is shown in the figure. The |Z| of the double-layer super-hydrophobic coating before the salt spray corrosion test is performed. 0.01 HZ The value is 1.37 × 10 11 Ω∙cm 2 .

[0073] Figure 6 The microscopic morphology and contact angle of the double-layer super-hydrophobic coating prepared in Example 1 of the present invention are shown in FIG. Figure 6 (a), (b), and (c) are the microscopic morphologies of the super-hydrophobic coating. It can be seen from the figures that the surface of the super-hydrophobic coating is rough; Figure 6 The static contact angle shown in (d) reaches 162.2° and the dynamic contact angle is 4.6°, indicating good hydrophobic function.

[0074] Example 6 A method for preparing a polyimide / polydimethylsiloxane super-hydrophobic composite coating comprises the following steps: S1: Under nitrogen protection, diamine monomer and polydimethylsiloxane are dissolved in an organic solvent, and then dianhydride monomer is added in batches, stirred for reaction, and a polyimide / polydimethylsiloxane prepolymer with a solid content of 10% is synthesized by solution polycondensation; the polydimethylsiloxane accounts for 10% of the total mass of the diamine monomer and the dianhydride monomer.

[0075] S2: 0.1 mg of modified GO was added to 1.0 mL of organic solvent, and then ultrasonically dispersed for 10 min to obtain an organic dispersion of modified GO, i.e., a functional filler pre-dispersion liquid, and then the organic dispersion of modified GO was added to the polyimide / polydimethylsiloxane prepolymer, and ultrasonically dispersed for 15 min to obtain a composite bottom layer slurry with a solid content of 8%, i.e., a polyimide / polydimethylsiloxane prepolymer composite slurry containing modified GO, and the composite bottom layer slurry was coated on the surface of the substrate, and the sprayed sample was placed for 1 hour at room temperature to achieve surface drying, and after a program thermal imidization treatment, a composite bottom layer with a thickness of 1 μm was obtained, i.e., a polyimide / polydimethylsiloxane composite coating. The thermal imidization process includes volatilizing a large amount of solvent at 80°C and then completing imidization at 200°C.

[0076] In the modified GO, the mass ratio of the modifying agent to GO is 1 wt %, and the mass fraction of the modified GO in the polyimide / polydimethylsiloxane prepolymer is 0.01 wt %.

[0077] S3: Coating a PU intermediate layer on the surface of the composite bottom layer, and then coating the adhesive and a suspension of fluorinated modified SiO2 on the surface of the PU intermediate layer, and curing at room temperature for 24 hours to obtain the polyimide / polydimethylsiloxane super-hydrophobic composite coating. In this step, the curing temperature and time depend on the properties of the adhesive. The fluorinated modified SiO2 accounts for 0.01wt% of the adhesive mass. Example 7 A method for preparing a polyimide / polydimethylsiloxane super-hydrophobic composite coating comprises the following steps: S1: Under nitrogen protection, diamine monomer and polydimethylsiloxane are dissolved in an organic solvent, and then dianhydride monomer is added in batches, stirred for reaction, and a polyimide / polydimethylsiloxane prepolymer with a solid content of 50% is synthesized by solution polycondensation; the polydimethylsiloxane accounts for 30% of the total mass of the diamine monomer and the dianhydride monomer.

[0078] S2: 10 mg of modified GO was added to 1.0 mL of organic solvent, and then ultrasonically dispersed for 60 min to obtain an organic dispersion of modified GO, i.e., a functional filler pre-dispersion liquid, and then the organic dispersion of modified GO was added to the polyimide / polydimethylsiloxane prepolymer, and ultrasonically dispersed for 60 min to obtain a composite bottom layer slurry with a solid content of 20%, i.e., a polyimide / polydimethylsiloxane prepolymer composite slurry containing modified GO, and the composite bottom layer slurry was coated on the surface of the substrate, and the sprayed sample was placed for 2 hours at room temperature to achieve surface drying, and after a program thermal imidization treatment, a composite bottom layer with a thickness of 150 μm was obtained, i.e., a polyimide / polydimethylsiloxane composite coating. The thermal imidization process includes volatilizing a large amount of solvent at 135°C and then completing imidization at 300°C.

[0079] In the modified GO, the mass ratio of the modifying agent to GO is 6.5wt%, and the mass fraction of the modified GO in the polyimide / polydimethylsiloxane prepolymer is 1.50wt%.

[0080] S3: Coating a PU intermediate layer on the surface of the composite bottom layer, and then coating the adhesive and a suspension of fluorinated modified SiO2 on the surface of the PU intermediate layer, and curing at room temperature for 24 hours to obtain the polyimide / polydimethylsiloxane super-hydrophobic composite coating, wherein the curing temperature and time depend on the properties of the adhesive. Wherein, the fluorinated modified SiO2 accounts for 1.50wt% of the adhesive mass.

[0081] Example 8 A method for preparing a polyimide / polydimethylsiloxane super-hydrophobic composite coating comprises the following steps: S1: Under nitrogen protection, diamine monomer and polydimethylsiloxane are dissolved in an organic solvent, and then dianhydride monomer is added in batches, stirred for reaction, and a polyimide / polydimethylsiloxane prepolymer with a solid content of 30% is synthesized by solution condensation; the polydimethylsiloxane accounts for 20% of the total mass of the diamine monomer and the dianhydride monomer.

[0082] S2: 5 mg of modified GO was added to 1.0 mL of organic solvent, and then ultrasonically dispersed for 30 min to obtain an organic dispersion of modified GO, i.e., a functional filler pre-dispersion liquid. The organic dispersion of modified GO was then added to the polyimide / polydimethylsiloxane prepolymer, and ultrasonically dispersed for 40 min to obtain a composite bottom layer slurry with a solid content of 15%, i.e., a polyimide / polydimethylsiloxane prepolymer composite slurry containing modified GO. The composite bottom layer slurry was coated on the surface of the substrate. At room temperature, the sprayed sample was placed for 1.5 hours to achieve surface drying. After a program thermal imidization treatment, a composite bottom layer with a thickness of 80 μm was obtained, i.e., a polyimide / polydimethylsiloxane composite coating. The thermal imidization process includes volatilizing a large amount of solvent at 100°C and then completing imidization at 250°C.

[0083] In the modified GO, the mass ratio of the modifying agent to GO is 3wt%, and the mass fraction of the modified GO in the polyimide / polydimethylsiloxane prepolymer is 1.0wt%.

[0084] S3: Coating a PU intermediate layer on the surface of the composite bottom layer, and then coating the surface of the PU intermediate layer with a suspension of an adhesive and fluorinated modified SiO2, and curing at room temperature for 24 hours to obtain the polyimide / polydimethylsiloxane super-hydrophobic composite coating, wherein the curing temperature and time depend on the properties of the adhesive. Wherein, the fluorinated modified SiO2 accounts for 1wt% of the adhesive mass.

[0085] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a polyimide / polydimethylsiloxane super-hydrophobic composite coating, characterized in that: The following steps are involved: S1: Under nitrogen protection, dissolving diamine monomer and polydimethylsiloxane in an organic solvent, then adding dianhydride monomer in batches, stirring and reacting, to obtain a polyimide / polydimethylsiloxane prepolymer; S2: adding the organic dispersion of modified GO to the polyimide / polydimethylsiloxane prepolymer to obtain a composite bottom layer slurry, coating the composite bottom layer slurry on the surface of the substrate, and obtaining a composite bottom layer after a program thermal imidization treatment; the modification reagent of the modified GO includes at least one of POSS, a silane coupling agent, a chain alkyl amine and a chain alkyl isocyanate, and the number of carbon atoms on the chain alkyl in the chain alkyl amine and the chain alkyl isocyanate is 7 to 18; S3: coating the adhesive and the suspension of fluorinated modified SiO2 on the surface of the composite bottom layer, and curing at room temperature to obtain the polyimide / polydimethylsiloxane super-hydrophobic composite coating.

2. The method for preparing a polyimide / polydimethylsiloxane super-hydrophobic composite coating according to claim 1, wherein The polydimethylsiloxane accounts for 10% to 30% of the total mass of the diamine monomer and the dianhydride monomer.

3. A method for preparing a polyimide / polydimethylsiloxane super-hydrophobic composite coating according to claim 1, characterized in that, The diamine monomer is a fluorine-containing diamine monomer and / or the dianhydride monomer is a fluorine-containing dianhydride monomer.

4. A method for preparing a polyimide / polydimethylsiloxane super-hydrophobic composite coating according to claim 1, characterized in that, In the modified GO, the mass ratio of the modifying agent to GO is 1 wt% to 6.5 wt%.

5. A method for preparing a polyimide / polydimethylsiloxane super-hydrophobic composite coating according to claim 1, characterized in that, In step S2, the mass fraction of the modified GO in the polyimide / polydimethylsiloxane prepolymer is 0.01wt%~1.50wt%.

6. A method for preparing a polyimide / polydimethylsiloxane super-hydrophobic composite coating according to claim 1, characterized in that: The thickness of the composite bottom layer is 40-50 μm.

7. A method for preparing a polyimide / polydimethylsiloxane super-hydrophobic composite coating according to claim 1, characterized in that: The preparation process of the fluorinated modified SiO2 is as follows: sodium methylsiliconate is added to a dispersion of SiO2 particles, and after stirring evenly, 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane and tetraethoxysilane are added, and the reaction is stirred at room temperature to obtain the fluorinated modified SiO2; the SiO2 particles include at least one of a particle size of 7~500nm and 2~20μm; when the SiO2 particles have a particle size of 7~500nm and 2~20μm, the mass percentage of SiO2 particles with a particle size of 7~500nm is 70%~85%, and the mass percentage of SiO2 particles with a particle size of 2~20μm is 15%~30%.

8. A method for preparing a polyimide / polydimethylsiloxane super-hydrophobic composite coating according to claim 1, characterized in that: In the suspension of the adhesive and fluorinated modified SiO2, the fluorinated modified SiO2 accounts for 0.01wt% to 1.50wt% of the mass of the adhesive.

9. A method for preparing a polyimide / polydimethylsiloxane super-hydrophobic composite coating according to claim 1, characterized in that: In the step S3, before coating the adhesive and the suspension of fluorinated modified SiO2 on the surface of the composite substrate, a PU intermediate layer is coated on the surface of the composite substrate, and then the adhesive and the suspension of fluorinated modified SiO2 are coated.

10. A polyimide / polydimethylsiloxane super-hydrophobic composite coating, characterized in that: The composite coating is prepared by the method according to any one of claims 1 to 9; the contact angle of the composite coating is 153 to 162°, and after 90 days of neutral salt spray test, the low-frequency impedance value of the composite coating is 9.81 × 10 9 Ω⋅cm 2 .

Citation Information

Patent Citations

  • Hydrophobic polyimide film and preparation method thereof

    CN106905557A

  • Preparation method of phenyl silsesquioxane / oxidized graphene / polyimide three-phase compound film

    CN108250749A

  • Preparation method of graphene modified polyimide composite film

    CN112795036A

  • SiO2 hyperbranched polymer / polyimide composite film and preparation method thereof

    CN118374149A

  • Multi-functional silizane-based coatings and materials

    US20230323155A1

Cited By

  • Solvent type aerogel anti-corrosion and wear-resistant coating as well as preparation method and application thereof

    CN120665508A